Analisis Variasi Abu Batu sebagai Substitusi Parsial Agregat Halus Terhadap Kuat Tekan Beton Self Compacting Concrete (SCC) - I Made Karya Jurdiawan; Kasmat Saleh Nur; Sartika Dewi Usman (Transbahasa, 2026)
Self-Compacting Concrete (SCC) is designed to flow and consolidate under its own weight without mechanical vibration while maintaining high workability. The properties of SCC are strongly influenced by the characteristics of fine aggregate. Stone ash, which has fine particles and a rough surface texture, has the potential to be used as a partial replacement for fine aggregate. This study investigated the effect of stone ash substitution on the compressive strength and fresh properties of SCC in accordance with the European Federation of National Associations Representing for Concrete (EFNARC) 2005 criteria. Stone ash was substituted at 0%, 5%, 10%, 15%, and 20% of the fine aggregate content. Fresh concrete tests included slump flow, T₅₀₀, J-Ring, and GTM Screen Ability, while compressive strength was tested at 28 days. The results showed that all mixtures met the slump flow, viscosity, and GTM Screen Ability requirements. However, the 5% variation showed less satisfactory performance in the T₅₀₀ test, and the 5%, 10%, and 15% variations were classified as Category III (poor) in the J-Ring test. Compressive strength increased at 5%, 10%, and 15% substitutions to 36.66 MPa, 35.80 MPa, and 35.94 MPa, respectively, compared to 30.19 MPa for the control mix. The highest strength was achieved at 5% substitution, representing a 21.43% increase. At 20% substitution, compressive strength decreased to 34.25 MPa. These findings indicate that limited stone ash substitution can enhance SCC compressive strength while maintaining acceptable fresh concrete performance.